Sovereignties in conflict: Socio-environmental mobilization and the glaciers law in Argentina - Christel, Lucas Gabriel (2017)
Until 2010, the cycle of socio-environmental mobilization in Argentina against transnational mining that began in 2003 had influenced legislative power only at subnational levels. The enactment of the Glaciers Law in 2010 constituted the first time that socio-environmental mobilization successfully influenced legislative power at the federal level. This article makes a double contribution to the analysis of this type of conflict. In theoretical terms, through the notion of "sovereignties in conflict", it problematizes the question of sovereignty in relation to socio-environmental conflicts, a dimension currently absent in studies of this kind. In empirical terms, it carries out a study of the enactment of the Glaciers Law. The principal argument is that the greater influence of socio-environmental mobilization on federal legislative power was made possible by the higher degree of openness to various viewpoints at this level, in contrast to that observed at subnational levels, and by the more successful organization and articulation of socio-environmental mobilization in this broader context.